Pengaruh Teknologi dan Globalisasi terhadap Budaya Lokal Anak Sekolah Dasar di indonesia - Magdalena Savira Balibo; Melania Jena Pinda; Susanti Wawa; Dietrick Micelle Aurelia pellondou; Gaudensius J. L. Koten (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The era of globalization and rapid digital advancement has brought significant impacts on various aspects of life, particularly the local culture of primary school-aged children in Indonesia. While technology offers benefits such as easier access to information and broader perspectives, massive exposure to global culture through digital media poses a serious threat to local wisdom values that should serve as the foundation for character development among the younger generation. This study aims to: (1) analyze trends in sociocultural value shifts due to technology among primary school children based on scientific literature; (2) evaluate factors that make children more susceptible to adopting global culture over local culture; and (3) formulate a model for integrating local wisdom into a digital-based education system as a strategic recommendation for educators and policymakers. This research employs a library research approach with a descriptive-analytical qualitative content analysis design. Data sources consist of reputable national and international journal articles relevant to sociocultural topics of primary school children in the digital era. The findings indicate that technology and globalization have caused a tangible shift in children's local culture, reflected in diminishing interest in traditional games, folklore, and local wisdom values. The primary factors driving global cultural adoption include dominance of the digital environment, insufficient parental supervision, and inadequate integration of local culture in digital educational content. As a strategic response, this study recommends integrating local wisdom into digital-based curricula, strengthening the roles of teachers and parents as cultural mediators, and developing character education policies adaptive to technological advancements.